CANDY’S BOWL: POLITIK KERUKUNAN BERAGAMA DI INDONESIA - Munawar Ahmad (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2013)
Politics Candy Bowl ‘s start from the assumption that the dispute is social fact that can not be avoided . Disputes will lead to destruction if all parties mutually develop destructive spirit , beat and kill each other . These consequences also can not be avoided and it would be worse if those entities become part of instrumentalization of interest, so thing suppose to be easily resolved become more difficult to be resolved due to the dominacy of the interests behind it. The politic of Agonism requires a plural social life like candy ‘s bowl where all the candy`s colors still exist, but they are in a protected space which guarantee the independence`s life of all elements without reduced by ideological values beyond them selves.